Pemetaan Perilaku Pengguna Ruang Pasar Tradisional Rimo, Aceh Singkil - Cindy Ferantika; Cut Nursaniah; Masdar Djamaludin (Jurnal RAUT, 2022)
The traditional market is an architectural space that has a distinctive atmosphere because it accommodates various user characters with various activities in it, thus forming a distinctive pattern of behavior when interacting with the market environment. The problem that occurs in the Rimo traditional market is the mismatch between market space and its function, such as a lot of space used by users for free parking, or pedestrian circulation space that is used as an additional stall for traders, causing chaos. This study aims to produce a mapping of the behavior of Rimo traditional market users using the place centered mapping method. Data collection was carried out by observing several points that were crowded with visitors, supported by in-depth interviews with formal traders and buyers. The conclusion of this study shows that the conditions and facilities of the Rimo Market are not adequate to accommodate various types of activities and behaviors of traders and buyers so that many behaviors are not in accordance with the function of the place. The results of the study can be a reference for the government in planning and managing traditional markets so that they can improve the quality of their space.